ANALYSIS OF PROCESSES OF TECHNICAL CONDITION DETERIORATION FOR COMPLEX TELECOMMUNICATION AND RADIOELECTRONIC SYSTEMS - Zaliskyi, Maksym; Solomentsev, Oleksandr; Zuiev, Oleksii; Petrova, Yuliia (Science-based technologies, 2021)
The article is devoted to the solution of the scientific and practical problem of developing procedures for statistical data processing on the reliability of telecommunications and radioelectronic systems in case of deterioration of their technical condition and general redundancy of equipment. It is known that the use of telecommunication and electronic systems in industrial activities tends to expand every year. Therefore, a main requirement for these systems is to increase the reliability of their operation, especially when they are used for critical infrastructure objects. One way to increase reliability is redundancy. Despite the use of various methods to increase reliability, the technical condition of telecommunications and electronic systems can still deteriorate due to the inevitable failures and damages, the human factor and the environment conditions, instability of the power system and other factors. The process of deterioration is usually associated with the transition from the stage of normal operation to the stage of wear out. This process can be visually detected by observing the reliability indicators, first of all the failure rate, which after reaching a certain point in time begins to increase. The object of research of this article is redundant telecommunications and radioelectronic system, the technical condition of which at a random point in time begins to deteriorate. The initial data for the calculation is failure rate of the equipment. In addition, the article makes assumptions about the step-function model of technical condition deterioration, which is described by the two-dimensional Heaviside function. For this model, analytical formulas for the probability density functions for time to failure are found. This allowed the synthesis of the algorithm for statistical data processing in order to identify the deterioration of the technical condition of telecommunications and electronic systems. The synthesis was performed based on the usage of the optimal detection rule and theory of multi-alternative hypothesis testing. Analytical expressions for decisive statistics were obtained, and the values of decision thresholds were found by statistical simulation. In order to analyze the proposed procedure for statistical data processing, detection characteristics were constructed for different values of the initial parameters of the model. Construction of detection characteristics was performed based on statistical modeling. As a result of the computation, acceptable values of the probability of correct detection are obtained. In general, the results of research can be used to develop and improve the operation systems of aviation telecommunications and electronic equipment